Impact Evaluation of DOH's Implementation of Articles 6 and 11 of the Framework Convention of Tobacco Control - Valerie Gilbert Ulep; Nina Ashley Dela Cruz; Alfredo Jose C. Ballesteros; Alyssa Cyrielle B. Villanueva; Clarisa Joy A. Flaminiano (Philippine Institute for Development Studies (PIDS), 2023)
Many non-communicable diseases (NCDs), while preventable, are caused by modifiable behavioral risk factors which include harmful consumption of alcohol, physical inactivity, tobacco use, and unhealthy diet. Tobacco use has been one of the biggest public health threats linked with NCDs killing more than 8 million people worldwide annually, with 7 million deaths associated with direct tobacco use, and 1.2 million from non-smokers exposed to second-hand smoke. It is estimated that there are 1.3 billion tobacco users globally, 80 percent of which reside in low- and middle-income countries. There are also considerable amounts of economic costs and burden, especially for families, arising from significant expenses for health care in treating tobacco-related diseases, and losses in human capital from morbidity and mortality. Published studies on the impact of the Sin Tax Reform Law in the Philippines remain sparse and therefore warrant a systematic review of the landscape of local evidence available, and this paper examined the impact of tobacco taxation and progress on the implementation of the World Health Organization (WHO) Framework Convention on Tobacco Control (FCTC) Article 6 on tobacco taxation. The systematic search yielded a total of 103 records (17 peerreviewed articles; 86 gray literature). Upon screening against eligibility criteria, a total of 25 records were included. To capture the breadth of evidence, this review did not exclude studies on the sole basis of quality, hence the review includes a mix of peer-reviewed literature, and both published and unpublished gray literature. The review found that, consistent with the existing literature outside the Philippines, cigarette consumption is price inelastic and responsive to an increase in excise taxes. Consumption is also affected by other determinants such as gender, educational level, and income classification. While illicit trade was found to have increased after implementation of the Sin Tax Reform Law, it was emphasized that there was no direct relationship between illicit trade and excise tax increases given the data and evidence. Lastly, excise taxes generated a dramatic increase in government revenues earmarked for alternative livelihood programs for tobacco farmers and healthcare expenditures.
Keywords: 330; systematic review; sin tax reform; WHO FCTC; tobacco taxation